Polo-like kinase 1 coordinates biosynthesis during cell cycle progression by directly activating pentose phosphate pathway. Issue 1 (December 2017) - Ma, Xiaoyu; Wang, Lin; Huang, De; Li, Yunyan; Yang, Dongdong; Li, Tingting; Li, Fudong; Sun, Linchong; Wei, Haoran; He, Kun; Yu, Fazhi; Zhao, Debiao; et al.
Abstract Two hallmarks for cancer cells are the accelerated cell cycle progression as well as the altered metabolism, however, how these changes are coordinated to optimize the growth advantage for cancer cells are still poorly understood. Here we identify that Polo-like kinase 1 (Plk1), a key regulator for cell mitosis, plays a critical role for biosynthesis in cancer cells through activating pentose phosphate pathway (PPP). We find that Plk1 interacts with and directly phosphorylates glucose-6-phosphate dehydrogenase (G6PD). By activating G6PD through promoting the formation of its active dimer, Plk1 increases PPP flux and directs glucose to the synthesis of macromolecules. Importantly, we further demonstrate that Plk1-mediated activation of G6PD is critical for its role to promote cell cycle progression and cancer cell growth. Collectively, these findings establish a critical role for Plk1 in regulating biosynthesis in cancer cells, exemplifying how cell cycle progression and metabolic reprogramming are coordinated for cancer progression. Polo-like kinase 1 (Plk1) is a key regulator of mitosis. Here, the authors show that Plk1 activates the pentose phosphate pathway in cancer cells by directly phosphorylating glucose-6-phosphate dehydrogenase (G6PD) and that such activation is critical for cell cycle progression and cancer cell growth.